E-waste situation and current practices in Brazil - Souza, Ricardo Gabbay [UNESP] (Elsevier, 2019)
Brazil is a country with huge territory and a population of approximately 200 million people. It is considered the largest E-waste producer in Latin-America, with estimated 7 kg E-waste per capita, and also a receiver of illegal E-waste exports from other industrialized countries. Some aspects which influence E-waste generation in the country are the population consumption patterns, market prices and offers, and technological evolution of equipment with consequent obsolescence of others.
Keywords: Brazil; Dismantling; E-waste; Informal sector; Recycling